Ketahanan 25 Genotipe Tomat (Solanum lycopersicum Mill.) terhadap Pecah Buah dan Korelasinya dengan Karakter-karakter Lain - Wahyuni, Sri; Yunianti, Rahmi; Syukur, Muhamad; Witono, Joko Ridho; Aisyah, Syarifah Iis (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTFruit cracking is one of the major constraints in tomato production in lowland areas. This reduces fruit quality and quantity both as freshmarket and processed fruits. The objective of this study was to determine the resistance of 25 tomato genotypes to fruit cracking, correlation to others characters and their genetic similarity. The experiment was conducted from April until August 2012 at Leuwikopo Field Station, Bogor Agricultural University. A randomized complete block design was used with three replications. Fruit crack index was used to evaluate tomato fruit crack resistance. Correlation and impacts of variables were analyzed by path analysis. The genetic similarity was analyzed by clustering analysis. Result of resistance evaluation showed that fruit crack index of 25 tomato genotypes ranged from 0.00 to 20.58. Fruit crack index was directly related to percentage of fruit crack weight per plant, percentage of number of fruit crack per plant and total soluble solids. Cluster analysis showed that the genotypes could be clustered into four groups.Keywords: clustering analysis, genetic diversity, path analysis